KONTRIBUSI KECEPATAN LARI 60 METER DENGAN HASIL LOMPAT JAUH SISWA PUTRA KELAS VII SMP NEGERI 8 MANDAU - Safrizal, Safrizal; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: in the long jump students still can not say well, this is seen when doing long jump less good results achieved this problem due to several factors, but in this study only look at the running speed of 60 meters in the long jump results of students. then this research aims to determine whether there is the contribution of speed to run 60 meters and long jump results boys class VII SMP Negeri 8 Mandau, in this study a sample of the entire population of 14 male students of class VII SMP Negeri 8 Mandau. Samples 14, his instrument do a test run of 60 meters and long jump. then the type of study is a correlation. This is the kind of research is a correlational study to look at the contribution of between two or more variables. on this research, research data which has been collected and analyzed then the variable x is a running speed of 60 meters and into the variable y is the result of long jump. the results of calculations can be seen that large correlation value running speed of 60 meters with the results of the long jump boys seventh grade junior high school 8 Mandau is 0.435 or count r value of 0.662 in the table value (product moment) (5%) of = 0.532, or 0.662 > 0.532 it means r calculate> r table. Ho hypothesis testing criteria accepted if t is smaller than t table, but the results of the calculations show that (t> t table) or 3.05> 1.782, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha), namely " is a contribution to the running speed of 60 meter long jump results V11 grade male student SMP Negeri 8 Mandau. "accepted. Keywords: running speed of 60 meters, long jump results